RELAXATION PROCESSES IN THIN FILMS OF CRYOCONDENSATES OF ETHANOL IN THE REGION OF GLASS TRANSITION TEMPERATURE - Aldiyarov, A.U. (Recent Contributions to Physics, 2008)
The behavior of a viscous liquid near the glass transition temperature, in particular, a sudden deceleration of relaxation processes, as well as the nature of the glass transition itself, are perhaps the most interesting and deep unresolved issues in the physics of condensed matter, considered in the twentieth century [1-4]. This work is the result of an analysis of the first stages of the study of polyamorphic transformations in glass-forming substances, when the object of study is ethanol, which is in a solid state at low temperatures.